Autism: research into causes and intervention. - Baron-Cohen S (Pediatric Rehabilitation)
Autism spectrum conditions are neuro-developmental syndromes with strong heritability. Cognitive theories have had some success in explaining why the cluster of features should co-occur. Empathizing deficits have the potential to make sense of one triad of impairments (social difficulties, communication difficulties and imagining others' minds), and may have a brain basis in the amygdala and left medial frontal cortex. A strong systemizing drive may account for a distinct triad of strengths (good attention to detail, deep, narrow interests and islets of ability). The brain basis of systemizing is yet to be understood. Family genetics studies suggest that these same cognitive dimensions (reduced empathizing alongside a strong drive to systemize) may also characterize the 'broader phenotype' among first-degree relatives. Molecular genetic studies are underway and any candidate genes for autism will ultimately need to be tested in relation to the observed differences in the brain, cognition and behaviour. The ethics of genetic screening or gene therapy should be thought about well ahead of these becoming available, since there is by no means any consensus that these would be desirable given the wide range of phenotypic traits, not all of which are disabling. Future research will need to focus on evaluating the extent to which any form of intervention reduces the triad of impairments whilst supporting the triad of strengths.